Understanding phase-transfer catalytic synthesis of fullerenol and its interference from carbon dioxide and ozone - Chokaouychai, Sirikanya; Zhang, Qi (Springer, 2020)
Phase-transfer catalytic reaction involving the use of tetrabutylammonium hydroxide (TBAH) as catalyst and sodium hydroxide (NaOH) solution as the source of hydroxide ions is among the popular choices for synthesis of fullerenol, the polyhydroxylated fullerene. To further understand the process, two experiments were conducted to preliminarily explore the influences of the amount of TBAH and NaOH, respectively, in terms of the achieved level of hydroxylation (i.e. number of hydroxyl groups per fullerenol molecule). The process responded to the variation of the amount of TBAH (over a twofold series of 3–192 drops, average volume 0.0223 ± 0.0004 ml per drop) in a nonlinear manner with a local maximum achieved from 24 drops TBAH (giving 13 OH groups) and a local minimum from 48 drops (giving 8 groups). To the variation of the amount of NaOH (over the range of 0.5–8.0 ml NaOH), the fitted function of the process response resembled Freundlich adsorption isotherm, with an initially increasing trend before levelling off at 4.0 ml NaOH (giving 15 OH groups). It is therefore suggested that fullerene hydroxylation could be explained by liquid–solid adsorption. In addition, it was found that ambient carbon dioxide led to the existence of sodium carbonate in the bulk of the collected product (although not chemically bound). It was also discovered that ambient ozone adversely affected fullerenol synthesis by converting C60 fullerene into fullerene epoxide (C60O). The affected syntheses thus produced epoxide-containing fullerenol instead
Keywords: Fullerene epoxide; Carbon dioxide; Ozone; TBAH; Carbon nanomaterials; Fullerenol